Nitrification and denitrification in pond - Yuni Puji Pujihastuti (Jurnal Akuakultur Indonesia)
More of waste than pond aquacultutre system produced, will increase sedimentation in the bottom.  Ammonium and nitrite compounds are other forms of inorganic nitrogen in the pond. Nitrogen anorganic consist of ammonia, ammonium, nitrit, nitrat and nitrogen. Degradation of process metabolic biota culture waste can biologically be nitrat compound one of the forms that are not toxic in the nitrification process.  Five process of nitrogen biogeochemical cycle in the container cultivation is the amonification, nitrification, nitrogen assimilation, denitrification and nitrogen fixation. Nitrogen is the one of the compound in the overlay/ top stratification sediment.  Improvement of speed degradation will be success if the pond bottom on aerobic condition. Survival rate of tiger shrimp in the laboratory scale can be increase by administration of nitrification and denitrification bacteria should not just in the water kolom of pond engineering but also at the bottom pond layer at the preparation step.  Depht of the sediment 15 cm in day zero, intensive pond have been produced of nitrit and ammonium with the producing bacteria.  Application of nitrification and denitrification bacteria in the sediment and water coloum can be performed as the measurenment and evaluation nitrit, nitrat and ammonium abudance.